2022
DOI: 10.3389/fpubh.2022.967691
|View full text |Cite
|
Sign up to set email alerts
|

School adaptation and adolescent immigrant mental health: Mediation of positive academic emotions and conduct problems

Abstract: IntroductionImmigrant adolescents must adapt their physical and mental attitudes to attain healthy development due to dramatic changes in their living and learning environments after relocation. From the perspective of positive psychology, this study explored the specific influence of school adaptation on mental health among immigrant adolescents, mainly focusing on the mediating effects of positive academic emotions and conduct problems.MethodsWe selected primary and secondary school students from five reloca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Similarly, Silva et al (2021) identified academic adaptation as a predictor of psychopathology. Numerous studies also outlined the relationship between academic adaptation and mental health problems like depression and anxiety (Xie et al, 2022;Maroco et al, 2020;Çakici Eş et al, 2020). This suggests that experiences within the academic context such as understanding the structure of tertiary education and enjoying educational processes are important for mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Silva et al (2021) identified academic adaptation as a predictor of psychopathology. Numerous studies also outlined the relationship between academic adaptation and mental health problems like depression and anxiety (Xie et al, 2022;Maroco et al, 2020;Çakici Eş et al, 2020). This suggests that experiences within the academic context such as understanding the structure of tertiary education and enjoying educational processes are important for mental health.…”
Section: Discussionmentioning
confidence: 99%
“…In this high expectation situation, teenagers need to have su cient conditions and abilities to show adaptive behavior in accordance with social norms, otherwise they are prone to academic adaptation problems (Caixia, 2018), such as school curriculum challenges (Bergmann et al, 2019), test anxiety (Sander & de la Fuente, 2020), learning di culties (Minshall et al, 2021), Low academic achievements (Keddie, 2018;West & Sweeting, 2003). Academic adaptation problems are academic problems caused by non-intellectual factors, often combined with emotional distress and behavioral problems, including cheating in exams, inattention in class, incomplete homework, unstable academic performance, inability to concentrate, resistance to school and other attitudes, motivations and habits that hinder effective learning (Xie et al, 2022;. In order to pursue achievement, teachers and parents often increase children's learning courses in addition to regular classroom learning, reduce the time and extent of children's sports participation, and even form the stereotype that "children who exercise are often poor in homework, poor class students and behavioral deviation" (Hao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Academic achievement is understood as a multi-determined phenomenon and depends, above all, on fundamental variables such as family context (Eslava et al, 2016) and individual beliefs about school performance (Garcia & Boruchovitch, 2015). In addition, poor school adaptation is associated with negative psychological outcomes due to the specificities of schooling at this stage that affect the mental health of this population (Xie et al, 2022).…”
Section: Introductionmentioning
confidence: 99%